Law on accounting in the Republic of Serbia and application of IAS/IFRS - Anđelković, Danijela; Dimitrijević, Dragomir (Pravo, teorija i praksa, 2025)
In accordance with its legal accounting framework, the Republic of Serbia has adopted IAS/IFRS as the sole financial reporting framework for all entities, while taking into account certain formal specificities of medium-sized and small enterprises. The International Accounting Standards Board (IASB) played a key role in this approach. These initial observations aim to highlight the quality of financial statements as a result of the application of the current accounting legislation in the Republic of Serbia. The issue of comparability and harmonization of financial statements is particularly relevant to medium-sized and small enterprises, as well as to companies whose securities are listed on the stock exchange. Research findings suggest that the application of the existing legal framework-specifically the mandatory and exclusive use of IFRS-has become a limiting factor in the quality of financial statements and, consequently, their representational value. The thematic scope of this paper involves the application of a methodology based on the collection of secondary data from relevant domestic and international sources. Through processing and analysis, this information enables an assessment of the current state of financial reporting quality. From the perspective of financial information users-primarily investors and creditors-the second part of the paper presents research findings and proposes measures to improve accounting regulations with the aim of enhancing the quality of financial statements.